Primary lacrimal sac lymphoma: a case-based retrospective study in a Chinese population - Fang Bai; Hai Tao; Xi-Bin Zhou; Fei Wang; Peng Wang; Li-Hua Wang; Hong-Yang Zhang (International Journal of Ophthalmology, 2023)
AIM: To determine the clinical characteristics, pathological types, tumor markers, treatments, and outcomes of Chinese patients with primary lacrimal sac lymphoma. METHODS: This case-based retrospective study analyzed 15 Chinese patients with primary lacrimal sac lymphoma. The clinical data collected included gender, age at diagnosis, symptoms, imaging examination results, pathologic diagnosis, pathogen identification, tumor markers, treatments, follow-up, and prognosis. Descriptive statistics were used to characterize the patients. Progression-free survival (PFS) was defined as the time from surgery to the last follow-up, first record of tumor recurrence, or death. RESULTS: There were 7 males and 8 females with unilateral primary lacrimal sac lymphoma in the left eye (n=6) or right eye (n=9). The initial symptom in 13 patients was epiphora, and 2 patients had redness and swelling in the lacrimal sac area. All patients ultimately developed epiphora, and 12 had masses in the lacrimal sac area. Analysis of preoperative plasma tumor markers indicated 14 patients had elevated homocysteine, 9 had elevated β2-microglobulin, and 2 had elevated lactate dehydrogenase (LDH); 2 patients had elevations of all three markers, and 1 patient had no elevation of any marker. All patients underwent surgical resection and 12 patients received postoperative chemotherapy. The pathological types were DLBCL (n=8), MALT lymphoma (n=5), and NK/T-cell lymphoma, nasal type (n=2). The mean follow-up time was 25.8mo (range: 4-41) and 2 patients died. Seven patients who underwent mass excision combined with dacryocystorhinostomy (DCR) had no postoperative epiphora. Eight patients who only underwent mass excision had varying degrees of postoperative epiphora. Preoperative LDH elevation and NK/T-cell lymphoma, nasal type were associated with poor prognoses. CONCLUSION: Early diagnosis and treatment can lead to a good prognosis for most patients with primary lacrimal sac lymphoma. Mass resection combined with DCR can reduce the occurrence of post-surgical epiphora. The pathology type and tumor marker status are associated with prognosis.